PERANAN SEKTOR KEHUTANAN DALAM PEREKONOMIAN JAWA TIMUR, 2006 DAN 2010 (ANALISIS INPUT-OUTPUT) - ANTONI, ANTONI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
East Java Province is a province that has the largest forest area and the biggest timber production potential on Java island. But, the Central Statistics Agency (BPS) shows that the contribution of the forestry sector to the Gross Domestic Regional Product (PDRB) for the last seven is relatively small. This study is conducted to determine the actual role of forestry sector in East Java's economy, through its contribution to the PDRB, linkages with other sectors of the economy, and its ability to promote the economic growth. The data used in this study are the data from Input-Output Table of East Java Province in 2006 and 2010. Several analysis consisting of contribution analysis, multiplier analysis, linkage analysis, and key sectors analysis are performed by Rasmussen/Hirschman method. The analysis result shows that the contribution of forestry sector is the biggest to the economy of East Java province, either to output, intermediate demand, or final demand. In general, the forest industry has a greater output and income multiplier than primary forest. This reveals the forestry industry has a high capability to increase output and income. Backward linkage value of forestry sector is higher than its forward linkage. Based on key sectors analysis, the wood, furniture, and crafts industry belongs to leading sector category. On the other hand, the paper, lumber, and other forest products industry belongs to non-leading sector category.